Greener approach toward the generation of dimedone derivatives. Issue 2 (17th January 2018) - Arora, Deepika; Dwivedi, Jaya; Kumar, Sudesh; Kishore, Dharma
ABSTRACT: The use of dimedone in green chemistry has been described for the synthesis of selective heterocyclic motifs which are both pharmacologically and industrially important. The objective of this review is to summarize some of the selected recent advances of dimedone in the synthesis of organic compounds utilizing green chemistry procedures. GRAPHICAL ABSTRACT: